2023
DOI: 10.1029/2023ja031560
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric Temperature and ΣO/N2 Variations as Observed by GOLD and Compared to MSIS and WACCM‐X Simulations During 2019–2020 at Deep Solar Minimum

Abstract: The ultraviolet‐imaging spectrograph that comprises Global‐scale Observations of the Limb and Disk (GOLD) mission in geostationary orbit at 47.5°W longitude has taken full disk images at high cadence throughout the deep solar minimum period of 2019–2020. Synoptic (i.e., concurrent and spatially unified and resolved) observations of thermospheric temperature and composition at ∼150 km altitude are made for the first time, allowing GOLD to disambiguate temporal and spatial variations. Here we analyze the daytime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The O/N 2 from the coarse resolution simulation is larger than observations at all latitudes, with increasing bias at higher latitudes in the winter hemisphere. The over‐estimation is also seen when compared with GOLD observation (G. Liu et al., 2023). This ratio in the high resolution simulation shows an overall decrease, bringing it to better agreement with observations.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The O/N 2 from the coarse resolution simulation is larger than observations at all latitudes, with increasing bias at higher latitudes in the winter hemisphere. The over‐estimation is also seen when compared with GOLD observation (G. Liu et al., 2023). This ratio in the high resolution simulation shows an overall decrease, bringing it to better agreement with observations.…”
Section: Resultsmentioning
confidence: 87%
“…In the thermosphere, photochemistry and diffusive separation are the dominant processes controlling the composition, but transport processes of different spatial and temporal scales can cause significant variability. For example, O/N 2 , a measure of the relative abundance of atomic and molecular species, is known to vary on seasonal and semi‐annual scales (e.g., Fuller‐Rowell, 1998; G. Liu et al., 2023; D. J. Strickland et al., 2004). This is thought to be controlled by the variation of thermospheric general circulation, which causes more rigorous “stirring” during solstices when the circulation is strong (Fuller‐Rowell, 1998; Jones et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TDISK data have also been used to quantify changes in thermospheric neutral density and dynamics in response to the SpaceX launch time geomagnetic storm of 3-4 February 2022 (e.g., He et al, 2023;Kakoti et al, 2023;Laskar et al, 2023). TDISK data are used for validation of model simulations (e.g., Laskar et al, 2023;Liu et al, 2023) and thermospheric observations (Aryal et al, 2022;Cantrall & Matsuo, 2021;Park et al, 2022). It has been reported that GOLD TDISK data are high compared to MSIS2 model simulations (e.g., Laskar et al, 2023;Liu et al, 2023).…”
Section: Behavior Of Effective Neutral Temperaturementioning
confidence: 99%
“…TDISK data are used for validation of model simulations (e.g., Laskar et al., 2023; Liu et al., 2023) and thermospheric observations (Aryal et al., 2022; Cantrall & Matsuo, 2021; Park et al., 2022). It has been reported that GOLD TDISK data are high compared to MSIS2 model simulations (e.g., Laskar et al., 2023; Liu et al., 2023). GOLD TDISK have been used to show that there are hemispheric asymmetries in the duration of thermospheric summer, which varies with latitude and local time (e.g., Wang et al., 2023).…”
Section: Behavior Of Effective Neutral Temperaturementioning
confidence: 99%